Thermal processing of bone: in vitro response of mesenchymal cells to bone-conditioned medium. Issue 8 (August 2015) - Sawada, K.; Caballé-Serrano, J.; Schuldt Filho, G.; Bosshardt, D.D.; Schaller, B.; Buser, D.; Gruber, R.
Abstract The autoclaving, pasteurization, and freezing of bone grafts to remove bacteria and viruses, and for preservation, respectively, is considered to alter biological properties during graft consolidation. Fresh bone grafts release paracrine-like signals that are considered to support tissue regeneration. However, the impact of the autoclaving, pasteurization, and freezing of bone grafts on paracrine signals remains unknown. Therefore, conditioned medium was prepared from porcine cortical bone chips that had undergone thermal processing. The biological properties of the bone-conditioned medium were assessed by examining the changes in expression of target genes in oral fibroblasts. The data showed that conditioned medium obtained from bone chips that had undergone pasteurization and freezing changed the expression of adrenomedullin, pentraxin 3, BTB/POZ domain-containing protein 11, interleukin 11, NADPH oxidase 4, and proteoglycan 4 by at least five-fold in oral fibroblasts. Bone-conditioned medium obtained from autoclaved bone chips, however, failed to change the expression of the respective genes. Also, when bone-conditioned medium was prepared from fresh bone chips, autoclaving blocked the capacity of bone-conditioned medium to modulate gene expression. These in vitro results suggest that pasteurization and freezing of bone grafts preserve the release of biologically active paracrine signals, but autoclaving does not.